A study of thermal comfort enhancement by the optimization of airflow induced by a ceiling fan. Issue 4 (3rd July 2016) - Hsiao, Shih-Wen; Lin, Hsin-Hung; Lo, Chi-Hung
Abstract: In this study, the air flow generated by a ceiling fan inside a room is investigated by Computational Fluid Dynamics (CFD) simulation. In the model, a thermal mannequin sits in front of a computer desk with a rotating ceiling fan above the thermal mannequin around which the flow and thermal field was analyzed. The objective of this study is to optimize a ceiling fan's parameters which include the rotation speed, diameter, blade count, horizontal inclination angle, vertical inclination angle, camber angle, stagger angle, flow angles at inlet/ outlet, incidence angle, glide angle, etc. by conducting comprehensive CFD simulation. For a ceiling fan to generate a preferable flow and thermal field, the effect of convective heat transfer needs to be enhanced so that the air flow can effectively take the heat generated by a human body away. The CFD analyses provide a better understanding of the velocity and temperature distributions around a human body so that the effects of various fan parameters can be estimated. The results indicated that the airflow velocity on the rotation plane of a blade is the most important indicator. By changing the rotational speed in the simulation model, the resulting effects on thermal comfort characteristics can be investigated. It was found in this study that, the circulation of air is optimized by an optimal rotation speed at which the thermal characteristics are greatly enhanced while the comfort level perceived by a human body is kept to a reasonable extent. Since the cooling condition can be optimized without the need of turning on any air conditioner at a higher outside ambient temperature, the electric bill can be greatly reduced without affecting the degree of thermal comfort. The results of this study indicated that, a ceiling fan can keep the thermal comfort at a reasonable level and greatly save the power cost as compared to air conditioners.